2015
DOI: 10.1371/journal.pntd.0004069
|View full text |Cite
|
Sign up to set email alerts
|

Release of Small RNA-containing Exosome-like Vesicles from the Human Filarial Parasite Brugia malayi

Abstract: Lymphatic filariasis (LF) is a socio-economically devastating mosquito-borne Neglected Tropical Disease caused by parasitic filarial nematodes. The interaction between the parasite and host, both mosquito and human, during infection, development and persistence is dynamic and delicately balanced. Manipulation of this interface to the detriment of the parasite is a promising potential avenue to develop disease therapies but is prevented by our very limited understanding of the host-parasite relationship. Exosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
201
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(211 citation statements)
references
References 69 publications
10
201
0
Order By: Relevance
“…Future phenotypic anthelmintic screens for drug development should include growth and developmental assays as well as release of excretory substances and exosomes assay (54)(55)(56) in addition to motility screens.…”
Section: Discussionmentioning
confidence: 99%
“…Future phenotypic anthelmintic screens for drug development should include growth and developmental assays as well as release of excretory substances and exosomes assay (54)(55)(56) in addition to motility screens.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the mechanisms and the net fitness effects remain to be investigated for virtually all described cases of host manipulation. Multiple parasites of insects have been speculated to secrete chemical compounds for host manipulation (Libersat et al, 2009), T. gondii secretes peptides that interact in multiple ways with the host immune system (Leroux et al, 2015), and even the release of small RNAcontaining vesicles has been reported for the filarial parasite Brugia malayi (Zamanian et al, 2015). However, the detailed nature of these molecules and their modes of action in the host remain to be identified.…”
Section: Physiological Mechanismsmentioning
confidence: 99%
“…Whilst EVs secreted by helminths can be internalized by host cells and regulate host immune and inflammatory responses (2)(3)(4)(5)10), it is unclear to what extent Fasciola EVs contribute to maintaining a Th2/regulatory environment that is permissive to fluke survival and reproduction. Once we gain a better understanding of these issues, the selective disruption of key pathways involved in EV biogenesis, or blocking the EV-driven delivery of parasite immunomodulators to host cells, might prove to be an efficient way to achieve parasite control in the future.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Indeed, perturbing EV production to modulate their pathological effects is an attractive therapeutic option that has been successful in a number of diseases, including cancer (1). To the same extent, several studies have described the contribution of parasite-derived EVs to the modulation of the host immune system (2)(3)(4) or the pathological effects on host cells (5). Tools such as transcriptomics and proteomics, have been particularly useful for identification of the immunomodulatory molecules that parasites package into EVs (6).…”
mentioning
confidence: 99%